Mobility and Citizenship during Pandemics: The Multilevel Political Responses in South America - Brumat, Leiza; Finn, Victoria (PARTECIPAZIONE E CONFLITTO, 2021)
During the Covid-19 pandemic in 2020, (im)mobility policies affected individuals’ citizenship rights and movement within countries and across international borders. Prior to the pandemic, the mobility regime in South America was relatively open for regional migrants, bolstered on free residence and equal rights. In this analysis, we focus on human mobility and citizenship rights in South America by examining local and national government responses to Covid-19 between March and August 2020. Using databases, newspaper columns, government websites, and legislation, we outline the region’s travel restrictions and exceptions, closures and militarization of borders, internal movement procedures, and economic subsidies to ease Covid-19’s impact. While the regional mobility regime had already been under stress since 2015, exceptions to border closures and internal mobility further stratified people based on legal and economic statuses. Deeply affecting individual-state relations, access to mobility and citizenship rights such as labor, housing, and healthcare varied between nationals and non-nationals and between regular and irregular migrants. Reactions may have longer term effects, especially for Venezuelans, since the crisis created new inequalities and contradictions within the regional mobility regime, originally aimed at reducing them.